Empowering Educators: Uncovering the Transformative Role of ChatGPT in EFL Pre-Service Teacher Development - Sihombing, Filemon; Kusuma, I Putu Indra; Dewi, Kadek Sintya (STKIP AGAMA HINDU SINGARAJA, 2024)
AbstractThis qualitative descriptive research investigates the influence of ChatGPT on the professional development of pre-service teachers specializing in English as a Foreign Language (EFL), with a specific focus on pedagogical innovations. The study, conducted using a phenomenological research approach, involved seven participants enrolled in the